Establishing the Generic Structure Potential of Bidayuh Bau-Jagoi Oral Folk Narratives, Dondan - Campbell, Yvonne Michelle; Ghazali, Kamila; Sahuri, Sakina Sahuri Suffian (Issues in Language Studies, 2018)
This study aimed to establish the genre status of the Bidayuh oral folk narrative, known as dondan, with a focus on the Bau-Jagoi Bidayuh group. In order to analyse the genre status of the dondan, the Generic Structure Potential (GSP) is used. The analyses revealed that the dondan has a similar GSP to English Fairy Tales but differs in terms of one of the elements, the Placement, which is an obligatory element in the dondan. The study also revealed that the Semantic Attributes which realises these GSP elements are more culturally based. Although the GSP of the dondan is similar to English Fairy Tales, it is the optional elements that reflect the culturally related elements of the dondan especially the communicative purpose to educate and disseminate cultural knowledge. Future work on oral folk narrative should include in-depth analysis of lexicogrammatical items.